Administrative Traditions of China and Indonesia - Anwar Anwar; Rosidah Rosidah; Ayu N. Pramazuly; Refly Setiawan; Stanislav V. Mladenov (RUDN Journal of Public Administration, 2023)
Each country has a different administrative tradition, such as those found in China and Indonesia. The two countries are close to each other and have good relations to date. Chinese Confucian teachings that are still preserved today have brought this country to change. The method used in this study is a qualitative research method using a document or literature analysis approach. The use of this method aims to obtain material and empirical data obtained through journals and scientific papers, reports, books, and other documents related to the research being conducted. The results of the study explain that the evolution of administration in China occurred from generation to generation, giving the characteristics of each dynasty. Similar to China, in Indonesia, the people also adhere to Pancasila values and include these values in the administration of government in Indonesia. The Indonesian nation upholds ethnic differences and tolerance of religious differences. However, national values still refer to Pancasila ideology and do not use Confucian teachings in administering government in Indonesia.